Percepciones de crianza y paternidad en un grupo de hombres homosexuales (2018)
The objective of this study was to investigate the perceptions that a group of homosexual men had about parenting and parenthood; terms that, although could be confused as similar, present aspects that differentiate them. Through our research, we make evident that parenting can be understood as educational styles that parents use to guide their children, while parenthood is related to the gender roles commonly attributed to them. A closed questionnaire was applied to 86 homosexual men divided into three categories: In Categories 1 and 2, we inquired the perceptions of them and their nuclear families about the concept of "parenting", and in Category 3, the conception of "parenthood" costructed by these homosexual men based on cultural models in which they are circumscribed and their own experiences. The results in Category 1 indicate that economic income is the most important factor in raising a child and that having homosexual parents will not affect their identity and sexual orientation; Category 2 shows that most of the primary families of these men would not oppose the fact that they were parents and raised a child; and in Category 3 we found that the discourse about what it means for them to be a father has changed at present, since more than half agreed with the reversal of established gender roles.